2011
DOI: 10.4103/2228-7477.83505
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy logic controller for hemodialysis machine based on human body model

Abstract: Fuzzy controllers are being used in various control schemes. The aim of this study is to adjust the hemodialysis machine parameters by utilizing a fuzzy logic controller (FLC) so that patient's hemodynamic condition remains stable during hemodialysis treatment. For this purpose, a comprehensive mathematical model of the arterial pressure response during hemodialysis, including hemodynamic, osmotic, and regulatory phenomena has been used. The multi-input multi-output (MIMO) fuzzy logic controller receives three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…As it was mentioned, blood volume monitor (BVM) can be used as a controlling system for estimating each treatment symptom or each patient’s activity (such as drinking during dialysis), which can affect the patient’s blood water volume. In addition, a simple feedback can be obtained for the control system of the ultrafiltration rate from the blood water volume by BVM [6,7]. A separate block has been designed for this measurement in some hemodialysis machines [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was mentioned, blood volume monitor (BVM) can be used as a controlling system for estimating each treatment symptom or each patient’s activity (such as drinking during dialysis), which can affect the patient’s blood water volume. In addition, a simple feedback can be obtained for the control system of the ultrafiltration rate from the blood water volume by BVM [6,7]. A separate block has been designed for this measurement in some hemodialysis machines [9].…”
Section: Discussionmentioning
confidence: 99%
“…It is concluded that controlling the blood water volume is specifically important in the dynamic stability of the cardiovascular system [6-8]. To gain desired blood water volume, the relative blood water volume (RBV) is defined.…”
Section: Introductionmentioning
confidence: 99%
“…was accounted for by using Takagi-Sugeno (TS) fuzzy system approximated as Multi Input Single Output (MISO) TS fuzzy system according to: Gaussian membership function was adopted to reduce the effect of noise in the signal. It has low sensitivity to small changes in input parameters than the singleton membership function (Nafisi, Eghbal, Motlagh and Yavari, 2011). The two parameters that characterized Gaussian membership functions as shown in Equation 6are the center, 𝑐 and the width, 𝜎…”
Section: Model Developmentmentioning
confidence: 99%